MORPHO-HISTOLOGY OF THE PITUITARY GLAND AND ITS DEVELOPMENT IN CATLA CATLA (HAMILTON) - SUDHA, H. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The development of the pituitary gland in Catlacatla is studied in 8 successive stages, from the time of the formation of ectophyseal ananage at 5.8 mm long hatchling to the regionation of the different neuroendocrine components of the pituitary at 160 mm long immature under-yearlingfish. The pituitary gland in C. catla arises as a solidingrowth of cells from the ectodermal epithelium by the formation of the ectophyseal analage. The pituitary gland is of the leptobasic type having a stalk and is divisible into the adenohypophysis and the neurohpophysis. The adenohypophysis is divisible into the restral pars distalis, proximal pars intermedia. The RPD consists of prolactin cells and the adrenocorticotrophs. The proximal pars distalis consists of the gonadotrophs, somatotrophs and thyrotrophs. The pars intermedia consists of the chromophobes with scantly cytoplasm in the melanophores.